PENGARUH KUALITAS PELAYANAN, HARGA DAN FASILITAS TERHADAP KEPUASAN PASIEN RAWAT JALAN PADA RUMAH SAKIT IMELDA - Tambunan, Putri Handini; Silalahi, Donalson; Tarigan, Miska Irani; Tarigan, Imanuel; Sitompul, Pandapotan (UNIKA Santo Thomas, 2025)
This study aims to determine and explain the influence of service quality, prices and facilities on outpatient satisfaction at Imelda Hospital. Data was collected using surveys, documentation and interviews. The research approach used was quantitative, with 100 respondents selected using purposive sampling. The data in this study were analyzed using SPSS. The research results show that service quality, prices and facilities have a good influence. Together they have a positive and significant effect on patient satisfaction. The coefficient of determination value of 0.441 shows that 44.1% of patient satisfaction can be explained by service quality, price and facilities while the remaining 55.9% is explained by other factors such as trust, location and brand image.